Modern aspects of training of doctors and dentists-orthopedists in the system of postgraduate education - Біда, Віталій Іванович; Дорошенко, О. М.; Радько, В. І.; Леоненко, П. В.; Клочан, С. М.; Гурін, П. О.; Паливода, І. І.; Оснач, Р. Г.; Пальчиков, А. В.; Германчук, С. М.; Омельяненко, Ольга Анатоліївна (Actual Dentistry, 2018)
Introduction. The main goal of the postgraduate education of orthopedic dentists on the modern stage is high-quality training focused on the final goal – increasing the level of professional competence of doctors, which is generally accepted in world practice. Goal. Analysis of the dynamics and optimization dentists-orthopedists training in the system of postgraduate education at the Department of Prosthetic Dentistry DI NMAPO named P.L. Shupyk on cycles of thematic improvement on perspective, modern trends. The results of the study. Dentists-orthopedists during training on the cycles of thematic improvement at the Department of Prosthetic Dentistry ID NMAPO named P.L. Shupyk increase the theoretical knowledge will improve practical skills necessary dentist-orthopedist for self robots in medical institutions in the performance of a certain type of orthopedic surgery. Conclusions. Are trained on a series of thematic improvement on otopedicheskoy dentists who performed in the Department of Prosthetic Dentistry ID NMAPO named P.L. Shupyk dentists orthopedists get the latest information – deep and wide tint, with a maximum mastery of practicality Navikom to provide skilled and specialized care. Knowledge of dentists-orthopedists modern methods of diagnosis, treatment and profіlaktiki major dental diseases, will raise the quality of dental care during the preparation, planning and manufacturing dentures using topical methods. Key words: dentistry, dentist-orthopedist, thematic improvement.